Phosphorus-rich stars with unusual abundances are challenging theoretical predictions - Thomas Masseron; D. A. García-Hernández; Raúl Santoveña; Arturo Manchado; Olga Zamora; Minia Manteiga; Carlos Dafonte (Nature Communications, 2020)
Current models of Galactic chemical evolution under predict the phosphorus we observe in our Solar System. Here, the authors show the discovery of 15 phosphorus-rich stars with a peculiar abundance pattern that challenges the present stellar nucleosynthesis theoretical predictions, but which could explain the missing source of phosphorus in the Galaxy.